SISTEM PENDUKUNG KEPUTUSAN DENGAN METODA MULTI-CRITERIA DECISION MAKING ( MCDM) - Nur Heri Cahyana (Telematika, 2012)
Multicriteria decision making methods MCDM technique takes preference to the  idealsolution, TOPSIS is one of the more widely used MCDM methods in decision supportsystems. For the purpose of the work, the modified TOPSIS method into a form that canbe used for the implementation of web-based medical diagnosis system. In modifying TOPSIS method,  we utilize fuzzy logic te so users can more accurately describe their symptoms. Data provided by the modified TOPSIS method is often in proportion and maytake considerable time to produce alternative rankings. TOPSIS is suitable for parallel computing due to a combination of  matrix calculations. Therefore implemented a parallelcomputer so that a large number of input data can be handled simultaneously, it reduces the overall execution time. In addition, making the system more accessible MCDM. Web-based medical diagnosis system including user interface dynamically generated.